A meta-analysis of visual orienting in autism - Landry, Oriane; Parker, Ashton (Frontiers in Human Neuroscience, 2013)
Background: Visual orienting is inconsistently reported to be impaired in autism. Methods: We conducted a meta-analysis on visual orienting in autism. We focused on studies that used a Posner-type task. A total of 18 research papers published between 1993 and 2011 were included in our meta-analysis. We examined the effects of differences in experimental design as well as differences in participant samples. We examined both orienting reaction times of participants with autism, and the effect size relative to comparison group in each experiment. Results: We found that participants with autism oriented across conditions (mean orienting effect = 40.73 ms), which was of an overall smaller magnitude than that of comparison groups (Cohen’s d = .44). Participants with autism were most impaired on arrow cue tasks, and least impaired on eye-gaze cue tasks, more impaired with rapid trials, and the impairment increased with age. Conclusions: Variations in experimental design and participant age group contribute to whether participants with autism appear impaired at visual orienting. Critical gaps exist in the literature; developmental studies are needed across and comparing broader age ranges, and more attention should be focused on basic endogenous orienting processes.